E-Procurement Dalam Proses Pengadaan Barang dan Jasa di Kota Malang - Nurhasanah Nurhasanah; Ica Indah; Muhammad Kamil (Jurnal Ilmu Pemerintahan, 2025)
The success in government service is seen from the existing reality. The development of the city of Malang to achieve a Smart City is implemented through an Electronic-based system. Included in the procurement of goods / services in the city of Malang using the General Procurement Information System (SiRUP) which will announce the RUP data in Malang City. SiRUP itself is a web-based procurement information system application that is used as a method or tool to announce the RUP. This study aims to determine the implementation of the General Procurement Information System (SiRUP) in Malang. The method used in this research is qualitative through various journal literature and interviews. This study uses primary and secondary data relating to the Development of Information System for General Procurement Plans (SIRUP) to Improve Public Services in Malang City.